Making a meaningful difference through collaboration: The experiences of healthcare staff redeployed to a contact tracing and monitoring team as part of the COVID-19 response. Issue 3 (4th May 2023) - Evans, Sherryn; Shaw, Nicole; Veitch, Rachel; Layton, Melinda
ABSTRACT: During the coronavirus disease 2019 (COVID-19) pandemic, the health care system experienced unprecedented demands with many health care workers being redeployed. Although there are emerging studies investigating redeployment to acute care, the experience of redeployment to roles outside of these settings, such as to contact tracing and monitoring (CTM) teams, has not been reported. This research was designed to explore health care workers' experience of redeployment to a regional COVID-19 CTM team. Staff redeployed to this CTM team completed an anonymous online survey following the second wave of the COVID-19 pandemic in Victoria, Australia. The survey used open-ended questions to explore participants' perceptions of what did and did not work well during their redeployment. Inductive template thematic analysis of the data found that during their redeployment to CTM teams, participants experienced a sense of collaboration, the opportunity for professional growth, and the perception of making a meaningful contribution to the pandemic. Redeployed CTM team members also described a need to adapt to constant change and felt that the redeployment took a personal toll on them. The findings from this research may be useful to support preparedness of health care workers for redeployment in future complex or crisis situations.